Pregnancy rate of intrauterine insemination (IUI) - is it affected by inseminated motile sperm count and stimulation protocol?. (October 2020) - Kim, S.T.; Gibson, C. Barnwell; Carrozza, J.; Bowling, M.; Park, J.; Couchman, G.; Meyer, W.
Abstract : Objective: To compare IUI pregnancy rate by partner and donor sperm according to inseminated motile sperm count and ovulation induction protocol Design: Retrospective study by a private IVF center Materials and methods: 3, 028 IUI cycles (2, 284 cycles with partner sperm and 744 cycles with donor sperm) were analyzed. Ovulation induction was done using 5 mg of letrozole (Let) on cycle days 3 through 7, with 250 mcg recombinant hCG injected as instructed after follicle monitoring is done on day 12. A sequential (Seq) stimulation involves Let protocol, followed by 150 IU FSH daily from cycle day 7. Ultrasound monitoring is done on day 10 to determine further medication dosing, GnRH antagonist initiation, and monitoring. A controlled ovarian hyperstimulation (COH) cycle involves daily FSH injections at doses between 150 and 300 IU FSH, with monitoring beginning on day 7 to determine further medication dosing, GnRH antagonist initiation, and monitoring. All IUI procedures were performed approximately 36 hours after trigger. Pre-washed frozen sperm was thawed by agent's thawing protocol. Total motile sperm for insemination was counted after finishing sperm wash process. The statistical analysis was performed using t-test, chi-square, or z-test. A p value of <0.05 was considered statistically significant. Results: IUI pregnancy rate by using partner sperm was significantly lower (n=106, 3.8%) when inseminated motile sperm is <3 million (average 1.2±0.8 million). However, the pregnancy rate was dramatically increased (n=21, 19.0%) when 3 million motile sperm were inseminated. In donor sperm group, there is no significant difference of pregnancy rate according to inseminated motile sperm count because motile sperm is at least 6 million. In the IUI using partner sperm, the pregnancy rate in natural cycle group was significantly lower (n=35, 8.6%) than that in COH (n=808, 20.5%) and Seq (n=601, 22.1%), but not in Let (n=840, 15.0%) group (p<0.05). There is no significant difference of pregnancy rate between different ovulation induction protocol group. IUI pregnancy rate using donor sperm was not significantly different between ovulation induction group, COH (n=100, 25.0%), Seq (n=125, 23.2%) and Let (n=499, 19.2%) and natural cycle group (n=20, 10.0%) although it was slightly low. Average age of patients and inseminated motile sperm count was not significantly different in each ovulation induction group and natural cycle group of both partner and donor sperm group. Conclusions: IUI pregnancy rate is not affected by sperm count if at least 3 million motile sperm are inseminated. Pregnancy rate from natural cycle is low in both partner sperm and donor sperm cycle. There is no significant difference of pregnancy rate between ovulation induction protocols although the pregnancy rate in Let group is slightly lower than that in COH or Seq group.